Credit Guarantee Subrogation by Guarantee Companies in Credit Agreements in Small and Micro Enterprises - Marta S, R Adi (Dinasti Research, 2025)
Compared to large business actors, micro, small, and medium enterprises (MSMEs) still receive very small amounts of credit from banks. Banks face obstacles in distributing credit to micro, small, and medium enterprises (MSMEs) due to high cost of funds, no reports, business legality, and marketable collateral. Credit Guarantee is an activity in the form of providing guaranteed to help access credit to micro, small, and medium enterprises (MSMEs) that have feasible businesses but do not meet the technical requirements of banking, especially in fulfilling collateral. The purpose of this writing is to determine the subrogation in credit guaranteed by the Guarantee Company in the credit agreement of micro, small, and medium enterprises (MSMEs). The method uses a normative legal approach, which means that this research focuses on the application of principles or standards in Positive Law. In addition, this study uses a library research report, which is carried out by reviewing library materials or secondary data using the library research method. Subrogation or transfer of collection rights in the cooperation agreement between the Guarantor Company and the Guarantor Recipient or Creditor, that since the claim has been paid by the Guarantor to the Guarantor Recipient does not release the Guarantor from his obligation to pay off his debt and since the claim is paid then the Creditor is born into two Creditors, namely the Bank and the Guarantor Company